2022
DOI: 10.1001/jamaoto.2022.1939
|View full text |Cite
|
Sign up to set email alerts
|

Endotracheal Tube Size in Critically Ill Patients

Abstract: To determine if smaller endotracheal tubes are noninferior to larger endotracheal tubes with respect to critical illness outcomes. DESIGN, SETTING, AND PARTICIPANTSThis propensity score-matched retrospective cohort study included all adult patients who underwent endotracheal intubation in the emergency department or intensive care unit and received mechanical ventilation for at least 12 hours from June 2020 to November 2020 at a single tertiary referral academic medical center. EXPOSURES Endotracheal intubatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The study findings that patients with small-for-height ETTs did not experience higher rates of mortality, reintubation, tracheostomy, ventilator-associated pneumonia, or prolonged hospital stay provide a rationale for investigating the effect of tube size on associated quality-of-life outcomes. The present study did not incorporate patient-reported measures or quality-of-life outcomes.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…The study findings that patients with small-for-height ETTs did not experience higher rates of mortality, reintubation, tracheostomy, ventilator-associated pneumonia, or prolonged hospital stay provide a rationale for investigating the effect of tube size on associated quality-of-life outcomes. The present study did not incorporate patient-reported measures or quality-of-life outcomes.…”
mentioning
confidence: 88%
“…Little is known as to whether larger ETTs improve recovery. Esianor and colleagues found no difference in 30-day all-cause in-hospital survival between patients with small, appropriate, or large-for-height endotracheal tubes. If larger tubes do not improve survival, is survivorship a better focus?…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In Reply We greatly appreciate the response of Dr Brenner and colleagues to our recent study . We are in complete agreement about the potential harms of large endotracheal tubes (ETT), which are commonly used in routine clinical care.…”
mentioning
confidence: 90%